2013
DOI: 10.1017/s0954102013000217
|View full text |Cite
|
Sign up to set email alerts
|

Salinity evolution and mechanical properties of snow-loaded multiyear sea ice near an ice shelf

Abstract: Sea ice often forms attached to floating ice shelves. Accumulating snow can depress its freeboard, creating a flooded slush layer that may subsequently freeze to form snow ice, rejecting brine as it freezes. The resulting salinity profile determines the mechanical properties of the sea ice. We provide measurements of snow-loaded, multiyear sea ice from summer to winter. Brine from a slush layer is not completely expelled from the sea ice when the slush refreezes to form snow ice. Measurements of sea ice salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In March, FYI had a freezing rate of +0.8 cm d −1 , while SYI had a melt rate of −2.7 cm d −1 . A comparable rapid melt rate (2.3 cm d −1 ) of fast ice in March has been observed in other parts of the Antarctic, for example at McMurdo Sound (Gough and others, 2013). The freezing of SYI ice started when the ice thickness was ~0.6 m, in agreement with a modelled theoretical multi-year thermodynamic cycle of minimum ice thickness in Prydz Bay (Yang and others, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…In March, FYI had a freezing rate of +0.8 cm d −1 , while SYI had a melt rate of −2.7 cm d −1 . A comparable rapid melt rate (2.3 cm d −1 ) of fast ice in March has been observed in other parts of the Antarctic, for example at McMurdo Sound (Gough and others, 2013). The freezing of SYI ice started when the ice thickness was ~0.6 m, in agreement with a modelled theoretical multi-year thermodynamic cycle of minimum ice thickness in Prydz Bay (Yang and others, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Relative to a water column at its freezing point, this supercooled water increased sea ice growth by 9 ± 4 cm yr −1 at a distance of 100 km from the ice shelf edge, and by a greater amount closer to the ice shelf. Such increased growth likely contributes to the maintenance of landfast sea ice along the Victoria Land coast (see Figure ), a perennial feature of the region [see Gough et al ., ]. Increased growth is especially evident within kilometers of the ice shelf where we observed that the layer of incorporated platelet ice is more than 1 m thick.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, multiyear sea ice persisted and typically formed a band around the southern and western edges of the Sound [see, e.g., Gough et al ., ], with much of the extensive sea ice cover being attributed to the large tabular icebergs in the vicinity of McMurdo Sound during 2000–2005 [ Robinson and Williams , ]. However, in February 2011, an ice breakout left the Sound ice free.…”
Section: Ice Shelf Water Flow In Mcmurdo Soundmentioning
confidence: 99%
“…Surface water is reported as being colder by the end of summer than it had been during noniceberg years [ Robinson and Williams , ]. Not only altering oceanic conditions, the physical barrier created by the icebergs resulted in a limited capacity for expulsion of sea ice from McMurdo Sound [ Remy et al ., ; Gough et al ., ] permitting it to persist. We observed an increase in MY freeboard through the study period together with the large 2005 increase in area.…”
Section: Discussionmentioning
confidence: 99%
“…At comparison points where the temporal separation is less than 50 days, the mean freeboard retrieval within a radius of 850 m is derived. The repeat pass tracks and crossover points are displayed with the end of summer fast ice edges for each year (Figure ) [ Gough et al ., ]. Values for repeat pass and crossover tracks are displayed as pairs in Figure .…”
Section: Method‐1 Icesat Freeboard Retrievalmentioning
confidence: 99%